Unveiling Cerebral Leishmaniasis: Parasites and brain inflammation in Leishmania donovani infected mice - Melo, Guilherme D. [UNESP]; Goyard, Sophie; Fiette, Laurence; Boissonnas, Alexandre; Combadiere, Christophe; Machado, Gisele F. [UNESP]; Minoprio, Paola; Lang, Thierry (Springer Nature, 2017)
Visceral leishmaniasis (VL) is a systemic disease with multifaceted clinical manifestations, including neurological signs, however, the involvement of the nervous system during VL is underestimated. Accordingly, we investigated both brain infection and inflammation in a mouse model of VL. Using bioluminescent Leishmania donovani and real-time 2D-3D imaging tools, we strikingly detected live parasites in the brain, where we observed a compartmentalized dual-phased inflammation pattern: an early phase during the first two weeks post-infection, with the prompt arrival of neutrophils and Ly6Chigh macrophages in an environment presenting a variety of pro-inflammatory mediators (IFN-γ, IL-1β, CXCL-10/CXCR-3, CCL-7/CCR-2), but with an intense anti-inflammatory response, led by IL-10; and a re-inflammation phase three months later, extremely pro-inflammatory, with novel upregulation of mediators, including IL-1β, TNF-α and MMP-9. These new data give support and corroborate previous studies connecting human and canine VL with neuroinflammation and blood-brain barrier disruption, and conclusively place the brain among the organs affected by this parasite. Altogether, our results provide convincing evidences that Leishmania donovani indeed infects and inflames the brain.